Simmons Longitudinal Study: Adaptation and Development Across the Lifespan (New England, United States), Preschool Data, Wave 1, 1977 - Reinherz, Helen Z. ([Verlag nicht ermittelbar], 2009)
The Simmons Longitudinal Study (SLS) is a community-based study that has prospectively traced the life course of a single-aged cohort from childhood (age 5) to adulthood (age 26). Data were collected from multiple informants at seven major time points: age 5 (1977), age 6 (1978), age 9 (1980-1981), age 15 (1987), age 18 (1990), age 21 (1993-1994), and age 26 (1998). Since its inception in 1977, the SLS has utilized a multidisciplinary, multimethod approach, with the dual goals of: (1) tracing the development and course of academic difficulties, behavior problems, and psychopathology; and (2) identifying factors that promote health functioning from early childhood (age 5) to adulthood (age 26). The SLS has consistently emphasized the identification of modifiable social and environmental risk and protective factors that can be targeted directly in prevention and intervention programs. To date, SLS has published 50 journal articles and 9 book chapters. For this wave of the study, Wave 1, the original study group was comprised of every child who entered kindergarten in the fall of 1977 in one public school district in a northeastern town in the United States. Each child participated in state-mandated testing of health and development three months before the start of school. The mothers of respondents also completed questionnaires assessing demographics, health history, development, and behavior of their children.